Lecturers' Commitment to Organizational Change (C2C) A Field Study Among CAS Lecturers at UUM - Daif, Khalid (2010)
Organizational commitment has been identified as one of the factors determining the success or failure of any organization, thus research into elements affecting it is really important for management professionals. However, empirical research has been lacking in scope when looking at the commitment to organizational change parameters and variables. The present study examines the relationship between the organizational commitment and commitment to organizational change, looking at the same time at different variables affecting these two factors. This investigation specifically focuses on the world of academia in Malaysian context in order to contemplate the relationship between strategy importance (S.I), Fit of the change with strategy vision (F.V) and Job motivation (J.M) as predictors of lecturers’ commitment to change (C2C). Following personal data collection performed during one-to-one research sessions with the respondents, quantitative statistical analyses were carried out and descriptive analyses were performed, the relationships between the variables were examined using multiple regression methodology. The results of the study show that strategy importance (S.I), Fit of the change with strategy vision (F.V), and job motivation (J.M) are important in obtaining lecturers commitment to change with a difference of importance for each of C2C’s dimensions from one to another. The results offer insights for managers and identify opportunities for future empirical research on change initiatives in organizations, especially in academic context.